2011
DOI: 10.1523/jneurosci.0957-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Responses Correlate with Temporal Expectation in Monkey Primary Visual Cortex

Abstract: Gamma oscillations have been linked to selective attention. Here, we investigate the effects of expecting a behaviorally relevant event (a change in the fixation point) on the oscillatory patterning of the local field potential and spiking responses in V1. Three protocols were used. In the first protocol, fixation point change occurred at a fixed time point, enabling predictions on task timing. In the second, fixation point change occurred in trial blocks either early or late in the trial, allowing us to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 59 publications
10
80
1
Order By: Relevance
“…First, elevated narrowband gamma power was a major factor predicting stimulus detection, similar to the role of gamma in visual detection in primates (Fries, 2015;Lima et al, 2011;Womelsdorf et al, 2006). Second, pre-stimulus decorrelation-most prominent in FS neuronspreceded successful stimulus detection, as in primates (Cohen and Maunsell, 2009;Mitchell et al, 2009).…”
Section: Discussionmentioning
confidence: 73%
“…First, elevated narrowband gamma power was a major factor predicting stimulus detection, similar to the role of gamma in visual detection in primates (Fries, 2015;Lima et al, 2011;Womelsdorf et al, 2006). Second, pre-stimulus decorrelation-most prominent in FS neuronspreceded successful stimulus detection, as in primates (Cohen and Maunsell, 2009;Mitchell et al, 2009).…”
Section: Discussionmentioning
confidence: 73%
“…These results have been supported by studies in humans showing enhancement of the early visual P1 potential in response to targets with high temporal expectation (Doherty, Rao, Mesulam, & Nobre, 2005;Zanto et al, 2011). Additionally, studies in humans and nonhuman primates have shown that temporal expectation modulates anticipatory neural activity to enhance the perceptual processing of events occurring at expected times (Besle et al, 2011;Cravo, Rohenkohl, Wyart, & Nobre, 2013;Green & McDonald, 2010;Lima et al, 2011;Praamstra, Kourtis, Kwok, & Oostenveld, 2006;Praamstra & Pope, 2007;Stefanics et al, 2010;van Ede, de Lange, Jensen, & Maris, 2011).…”
Section: Introductionmentioning
confidence: 66%
“…Electrophysiological studies in nonhuman primates have shown that visual areas such as V1 (Lakatos, Karmos, Mehta, Ulbert, & Schroeder, 2008;Lima, Singer, & Neuenschwander, 2011;Shuler & Bear, 2006), V4 (Ghose & Maunsell, 2002), MT (Ghose & Bearl, 2010), and IT (Anderson & Sheinberg, 2008) are Citation: Rohenkohl, G., Gould, I. C., Pessoa, J., & Nobre, A. C. (2014). Combining spatial and temporal expectations to improve visual perception.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been focused on gamma LFP activity in cortical areas and their possible function, for example in coordinating activation between distant cortical areas (72)(73)(74). At the same time, it has been noted that gamma oscillations in sensory cortices tend to be poorly coupled to aspects of visual stimuli or decision-related task variables, calling into question whether they are sufficiently reliable indicators of cortical processing (75).…”
Section: Discussionmentioning
confidence: 99%